Comparison between old and new imaging modalities in the presurgical evaluation of children with intractable epilepsy - Yara Shaheen; Bassant Ibrahim; Walaa Elnaggar; Ismail Elantably; Ahmed Morsi; Michael Baghdadi; Mina Rizkallah; Hala Elhabashy; Marian Girgis (Egyptian Pediatric Association Gazette)
Abstract Background Drug-resistant epilepsy is characterized by the failure of adequate trials of two well-selected anti-seizure drugs with tolerable side effects. Surgical intervention is often performed to mitigate or stop seizures. Different imaging techniques are used to evaluate those patients presurgically. Herein, we aimed to describe the correlation between seizure semiology, long-term video-EEG and neuro-imaging modalities including high resolution three-dimensional structural brain MRI, ASL perfusion, brain volumetric analysis, and FDG-PET scans throughout the presurgical assessment of focal drug-resistant epilepsy patients. Methodology Here, 30 patients fulfilled the inclusion criteria were included from our pediatric neurology clinic in a period from November 2021 till May 2023. History taking, full examination, 6–24-h long-term video-EEG recording (including ictal and inter-ictal recordings) and multiple neuro-imaging modalities were obtained from all patients. Thirty patients underwent structural MRI brain imaging, 27 patients underwent volumetry studies, and 28 patients underwent magnetic resonance arterial spin labeling sequence. PET was done when no proper localization of seizures occurred (n = 10). Results Our multimodal methodology indicated that among patients with focal DRE, temporal lobe epilepsy was the prevailing, impacting 12 patients (40%), followed by frontal lobe epilepsy, impacting 9 patients (30%). There was concordance between ictal EEG and inter-ictal EEG regarding the affected side and the affected lobe. We also found concordance between structural MRI and ASL regarding the affected side and the affected lobe. In addition to between ASL are ictal EEG and PET scan. Conclusion Focal DRE patients necessitate meticulous multi-disciplinary assessment through detailed seizure semiology analysis, adequate long-term video-EEG monitoring, and thorough neuro-imaging including already established techniques such as structural MRI and 18f-FDG PET brain scans and also new emerging techniques such as ASL and automated brain volumetry. Given the benefits of those new techniques regarding image quality, elevated accessibility, and the elimination of intravenous contrast agents, they are optimally suited for pediatric neuro-imaging during the pre-surgical evaluation of focal DRE.